(untitled) (Journal of Advanced Research in Social Sciences, 2024)
Transport safety is crucial for social sustainability, especially in rapidly urbanizing developing cities. This study evaluates the safety of Amman, Jordan’s urban transport system, and its impact on residents’ quality of life. Using the Analytic Hierarchy Process (AHP), we identified and prioritized five key safety indicators: accident rates, fatalities and injuries, pedestrian safety, public perceptions of safety, and the presence of safety infrastructure. The findings revealed high accident rates, inadequate pedestrian infrastructure, and poor public perceptions of safety. These issues lead to high-stress levels, limited mobility, and increased reliance on private vehicles, exacerbating traffic congestion and environmental pollution. Recommendations include stricter road safety measures, upgraded pedestrian infrastructure, public awareness campaigns, and enhanced public transport services. This research highlights the need for coordinated efforts among government agencies, private sector partners, and the community to improve transport safety and quality of life in developing cities.